Infective endocarditis in infants and children in the Western Cape, South Africa: a retrospective analysis. (2nd October 2019) - Willoughby, Mark L.; Basera, Wisdom; Perkins, Susan R.; Comitis, George A. M.; Fourie, Barend; Lawrenson, John B.; Zühlke, Liesl J.
Abstract: Infective endocarditis is a microbial infection of the endothelial surface of the heart, predominantly the heart valves, that is associated with high mortality and morbidity. Few contemporary data exist regarding affected children in our context. Aims and Objectives: We aimed to describe the profile and treatment outcomes of infant and childhood endocarditis at our facilities. Methods: This is a retrospective analysis of infants and children with endocarditis at two public sector hospitals in the Western Cape Province of South Africa over a 5-year period. Patients with "definite" and "possible" endocarditis according to Modified Duke Criteria were included in the review. Results: Forty-nine patients were identified for inclusion; 29 had congenital heart disease as a predisposing condition; 64% of patients met "definite" and 36% "possible" criteria. The in-hospital mortality rate was 20%; 53% of patients underwent surgery with a post-operative mortality rate of 7.7%. The median interval from diagnosis to surgery was 20 days (interquartile range, 9–47 days). Valve replacement occurred in 28% and valve repair in 58%. There was a significant reduction in valvular dysfunction in patients undergoing surgery and only a marginal improvement in patients treated medically. Overall, 43% of patients had some degree of residual valvular dysfunction. Conclusion: Endocarditis is a serious disease with a high in-hospital mortality and presents challenges in making an accurate diagnosis. Despite a significant reduction in valvular dysfunction, a portion of patients had residual valvular dysfunction. Early surgery is associated with a lower mortality rate, but a higher rate of valve replacement compared with delayed surgery.